Relationship Between Learning Motivation and Learning Method Against Learning Achievement Student Semester Subjects Meteorology and Climatology at the University of PGRI Palembang 2015 - Hartono, Deni Puji (Universitas Pendidikan Ganesha, 2016)
Advanced Research aims to determine the relationship between learning motivation and learning on student achievement. The method used in this study is correlational method. The results showed that: (1) there is a very strong positive relationship between learning motivation and achievement of students. By calculating the correlation r arithmetic learning motivation is bigger than r table (rhitung 0,812> rtabel 0.213); (2) there is a strong positive relationship between learning and academic achievement of students. By calculating the correlation of r count how learning is bigger than r table (rhitung 0.851> 0.213 rtabel); and (3) there is a strong positive relationship between learning motivation and learning with the achievement of students. By calculating the correlation r arithmetic learning motivation and learning styles of students is greater than r table (rhitung 0.895> 0.213 rtabel) and (Fhitung = 162.7> Ftabel 3.11).Â Keywords: Motivation, How to Learn and Learning Achievement